2020
DOI: 10.1016/j.virusres.2020.198197
|View full text |Cite
|
Sign up to set email alerts
|

The role of dysregulated immune responses in COVID-19 pathogenesis

Abstract: Highlights The severity of COVID-19 depends on the individual's immune response. Differences between the immune responses of the lung in children and adults may be the reasons for clinical differences in the pathogenesis of COVID-19. Impaired immune regulation lead to induction an uncontrolled local and systemic immune response, ineffective inflammation and severe COVID-19 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 85 publications
0
61
0
1
Order By: Relevance
“…A way to reduce the severity and mortality generated by acute respiratory distress syndrome (ARDS) produced by SARS-COV 2 is to strengthen the immune system. ARDS produces a dysregulation of the immunological system, and in the most severe cases, the release of pro-inflammatory cytokines and loss of T-cells in the infected organism [ 52 ]. There is evidence of the antiviral effect of Nrf2 on respiratory syncytial virus infection [ 53 ] and on SARS-COV 1 [ 54 ].…”
Section: Mechanisms Of Action Of Sfn On Immune Systemmentioning
confidence: 99%
“…A way to reduce the severity and mortality generated by acute respiratory distress syndrome (ARDS) produced by SARS-COV 2 is to strengthen the immune system. ARDS produces a dysregulation of the immunological system, and in the most severe cases, the release of pro-inflammatory cytokines and loss of T-cells in the infected organism [ 52 ]. There is evidence of the antiviral effect of Nrf2 on respiratory syncytial virus infection [ 53 ] and on SARS-COV 1 [ 54 ].…”
Section: Mechanisms Of Action Of Sfn On Immune Systemmentioning
confidence: 99%
“…Both SARS-CoV-2- (such as viral mutations) and human-related factors (such as age, gender, genetic, immune status, comorbidities, obesity and smoking) contribute to the COVID-19 severity and outcomes [ 1 , 2 ]. Massive infiltration of lung alveoli with inflammatory cells such as monocytes, macrophages, lymphocytes, eosinophils and neutrophils occur during COVID-19 [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that doxycycline may have beneficial effects for people affected by the newly emerged coronavirus disease 2019 (COVID19) due to its antiviral and anti-inflammatory properties [ 52 , 53 ]. The latter seem particularly relevant, as dysregulation of the innate immune responses and the cytokine storm have been associated with severe COVID19 cases [ 54 ]. This notion may be supported by observational reports of apparent benefits of the use of doxycycline for treatment of COVID19 patients [ 55 ], despite the fact that the in vitro calculated ratios of Cmax/IC 50 and Cmax/IC 90 seemed too low to reach effective concentrations in human plasma to inhibit growth of SARS-CoV-2 in [ 33 ].…”
Section: Discussionmentioning
confidence: 99%